Non-traditional educational methods in teaching English to schoolchildren - Yunusova Barno Tulkunovna (Zien Journals, 2022)
This article analyzes the active use of innovative technologies for teaching foreign languages in the Republic of Uzbekistan
Keywords: foreign language; games; innovative technologies